Social Integration of Hearing-Impaired Students by Means of Health-Enhancing and Recreational Activities - Anna Orikhovska; Olena Andrieieva; Vitaliy Kashuba; Olena Lazarieva; Yurii Lytvynenko; Viktoria Kirichenko; Valerii Arefyiev; Inna Khrypko (OVS LLC, 2020)
Purpose: To substantiate and develop a program of health-enhancing and recreational physical activity for the social integration of students with hearing impairments in a higher education institution environment. Materials and Methods. The study involved 65 students with hearing impairments 17-18 years of age (30 males and 35 females). Theoretical analysis and generalization of special scientific and methodological literature, pedagogical experiment, anthropometric measurements of the hearing-impaired, Apanasenko's method, methods of mathematical statistics were used. Results. The structure and content of the program of health-enhancing and recreational physical activity for students with hearing impairments were scientifically substantiated and developed. The program takes into account the factors, principles, objectives, tasks, methods, organizational and socio-pedagogical conditions for its effective implementation in higher education institutions. The program includes a system for monitoring the results of its implementation and performance criteria. The effectiveness criteria for the health-enhancing and recreational physical activity program were identified as follows: social integration of hearing-impaired students, restoring their psycho-emotional state, and involvement of the young people in regular physical activity. Conclusions. The results of the study confirmed the effectiveness of the developed program of health-enhancing and recreational physical activity in a higher education institution for the social integration of hearing-impaired students.